![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^8+3x^4+4\)
\(=\left(x^8-x^6+2x^4\right)+\left(x^6-x^4+2x^2\right)+\left(2x^4-2x^2+4\right)\)
\(=x^4\left(x^4-x^2+2\right)+x^2\left(x^4-x^2+2\right)+2\left(x^4-x^2+2\right)\)
\(=\left(x^4+x^2+2\right)\left(x^4-x^2+2\right)\)
\(4x^4+4x^3+5x^2+2x+1\)
\(=\left(4x^4+2x^3+2x^2\right)+\left(2x^3+x^2+x\right)+\left(2x^2+x+1\right)\)
\(=2x^2\left(2x^2+x+1\right)+x\left(2x^2+x+1\right)+\left(2x^2+x+1\right)\)
\(=\left(2x^2+x+1\right)^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{2}{3}x-\frac{1}{9}x^2-1\)
\(=-\left(\frac{1}{9}x^2-\frac{2}{3}x+1\right)\)
\(=-\left[\left(\frac{1}{3}x\right)^2-2\cdot\frac{1}{3}x\cdot1+1^2\right]\)
\(=-\left(\frac{1}{3}x-1\right)^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(49\left(x-4\right)^2-9\left(x+2\right)^2\)
\(=\left(7x-28\right)^2-\left(3x+6\right)^2\)
\(=\left(7x-28-3x-6\right)\left(7x-28+3x+6\right)\)
\(=\left(4x-34\right)\left(10x-22\right)\)
\(=4\left(2x-17\right)\left(5x-11\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
=> M= x3.x3+x3.x
=x3(x3+1)